The integration of East Asian equity markets - Abidin, Zarina Zainal (ProQuest Dissertations & Theses Global, 2002)
"The dissertation comprises three essays on the East Asian market integration. Chapter 1 examines the differences in the degree of market integration for Indonesia, Korea, Malaysia, the Philippines, and Thailand for the pre-1997-crisis and the post-1997-crisis periods using a regime switching model for the period January 1986 to January 2001. The results suggest that three economies, which were ultimately rescued by the IMF, Indonesia, Korea, and Thailand, have become less integrated after the crisis. In contrast, the evidence suggests that Malaysia, which undertook capital control as a response to the crisis, is becoming more integrated in the post-crisis period. As for the Philippines' market, which has been under the supervision of the IMF for the past three decades, its degree of integration remains stable during the period under investigation. Chapter 2 examines the return and volatility spillover effects from the U.S. to Hong Kong market. A bivariate GARCH model is estimated within a Kalman filter framework on the daily returns for the Hang Seng and S&P500 indices for the period January 1, 1985 to January 31, 2001. The main finding of this chapter is that innovations from the U.S. market have greater impact on the returns than on the volatility of the Hong Kong market. Furthermore, the impact of the return spillover which has increased over the years, plays a significant role in the price determination of Hong Kong securities relative to local innovations. Chapter 3 examines the linkages between the Hong Kong and U.S. markets for the period January l, 1985 to January 31, 2001. Assuming high and low volatility regimes for the market returns, the nature of the correlations between the markets in the two regimes are examined. Furthermore, as a by-product of the two regime model, the interrelation between the probability of high volatility regime and the periods of recession is also considered. The key findings of this paper the correlations between the markets are higher during periods of high volatility and the probability of the low volatility regime in the Hong Kong market is correlated with U.S. GDP growth and not with Hong Kong GDP growth."